DETERMINANTS OF STROKE INCIDENCE IN THE COMMUNITIESAT PIDIE DISTRICT - Raiyan, Deka; Risnawati, Risnawati; RMR, Fahrul Rozi; Rizki, Muhammad; Khairunnisa, Khairunnisa; Heramuliati, Heramuliati; Sutifa, Cut Yuliza; Zahara, Amelia; Mailiana, Mailiana; Nazifa, Naurah; Maidar, Maidar (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2023)
Background: Stroke is currently ranks as the second leading cause of death globally, after ischemic heart disease, and is the main cause of serious disability. In 2022, there will be more than 12.2 million new stroke cases recorded every year in the world, one in four people over the age of 25 will have a stroke in their lifetime. This research aims to identify risk factors for stroke in the community in Pidie Regency, which will enable more appropriate preventive and treatment interventions through early detection. Method: This research method uses quantitative with a survey research design, namely a cross sectional study. The total sample was 54 respondents aged 25 years who received treatment at Community Health Centers and Hospitals in the Pidie Jaya area. Samples were taken using the Accidental Sampling technique. Results: the results showed that of the 54 respondents, 30 (55.56%) had suffered a stroke. The research results also showed that there was a relationship between age (p-value 0.00) and hypertension (p-value 0.00) with the incidence of stroke. Recommendation: It is hoped that health workers will provide education or information to the public about secondary prevention efforts (healthy lifestyle, and controlling risk factors) which can be done directly in the form of counseling or indirectly in the form of media such as advertisements, posters atau brochures